Peran Balanced Scorecard Terhadap Peningkatan Kinerja Organisasi di Sektor Publik: Studi Literatur - Nababan, Rohani Risnauli; Syahidah, Silke; Sudrajat, Sayidati Rahmatut Salitsa; Mirza. BR, Aryan Danil (Penerbit Goodwood, 2025)
Purpose: This study explores the role of BSC in improving both financial and non-financial organizational performance in public sector organizations. Methodology/approach: This qualitative research employs a literature study method and utilizes secondary data sources from various studies, including articles and books obtained from Google Scholar. Results/findings: The Balanced Scorecard (BSC) plays a very important role because it can help organizations improve their performance and realize better organizational governance. With proper and strategic implementation, the BSC helps organizations align goals and activities at all levels, increase accountability and transparency, and improve stakeholder satisfaction. Therefore, the BSC is not only a performance measurement tool but also a strategic management framework that drives continuous improvement and organizational effectiveness, making it highly relevant for public sector organizations seeking to enhance performance and effectively achieve their goals. Conclusion: The Balanced Scorecard (BSC) is an effective strategic tool for public sector organizations to enhance accountability, transparency, and overall performance. Despite implementation challenges, its benefits outweigh the difficulties, making the BSC a valuable framework for aligning vision, mission, and organizational goals toward more efficient and effective management. Limitations: The research uses a literature study method, so there is a possibility that there is a gap with the world of practice. Contribution: This study contributes to the performance literature, particularly in public sector organizations.